Dakwah Pemberdayaan Partisipasi Keluarga - Miharja, Sugandi (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2019)
This paper aims to describe the dynamics of family empowerment in supporting da'wah programs in the countryside. Changes to the order of life, including in the rural areas, need adaptation from the da'wah movement that can balance and fill the changes towards a more qualified society. The family is the smallest group component, at most, and is most directly related to da'wah activities in the countryside. Family participation as a subject and missionary partner will determine the overall success. The research method used is a qualitative approach with community empowerment interventions. The target community is religious leaders and the community of the da'wah congregation, including: DKM chairmen, the reciters of recitation, and the asatidz, worshipers of mothers and teenagers as well as children of pengajian worshipers. Data obtained in the form of social and religious activities that have taken place in the village of Mandalasari. First, Social and Religious Activities. Second, Da'wah activities based on Empowering Family Participation. Third, the Role and Obligations as Family Members in empowering da'wah. Writing can describe a case about empowering da'wah through family participation in the countryside. Abstrak Tulisan ini bertujuan untuk menggambarkan dinamika pemberdayaan keluarga dalam mendukung program dakwah di pedesaan. Perubahan pada tatanan kehidupan termasuk di pedesaan perlu adaftasi dari gerakan dakwah yang bisa mengimbangi dan mengisi perubahan menuju masyarakat yang lebih berkualitas. Keluarga merupakan komponen kelompok terkecil, paling banyak, dan paling berhubungan langsung dengan kegiatan dakwah di pedesaan. Peran serta keluarga sebagai subjek dan mitra dakwah menjadi sangat menentukan akan keberhasilan secara keseluruhan. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan intervensi pemberdayaan masyarakat. Masyarakat sasaran adalah tokoh-tokoh keagamaan dan masyarakat jamaah dakwah, meliputi: Para ketua DKM, Ibu-ibu penggerak pengajian, dan para asatidz, para jamaah Ibu-ibu dan remaja serta anak-anak jamaah pengajian. Data yang diperoleh berupa keegiatan sosial dan keagamaan yang telah berlangsung di Desa Mandalasari. Pertama, Kegiatan Sosial dan Keagamaan. Kedua, Kegiatan Dakwah berbasis Pemberdayaan Partisipasi Keluarga. Ketiga, Peran dan Kewajiban sebagai Anggota Keluarga dalam dakwah pemberdayaan. Tulisan dapat menggambarkan suatu kasus tentang dakwah pemberdayaan melalui partisipasi keluarga di pedesaan.